Pelatihan goal setting sebagai upaya meningkatkan keputusan karier siswa kelas XII SMA Muhammadiyah Al-Mujahidin Gunungkidul - Dian Juliarti Bantam; Muhammadh Erwan Syah (University of Muhammadiyah Malang, 2022)
One of the problems faced by class XII students of SMA Muhammadiyah Al Mujahidin Gunungkidul is confusion in determining career choices, such as majoring in college or going straight to work. Reinforced by the results of a questionnaire conducted by counseling teachers on January 13, 2020. The results showed that 35% of students were able to make career choices, while 55% of students had not been able to make career choices, and 15% were hesitant in making career choices. Departing from this, the service team consisting of 2 lecturers and 2 students of the Psychology Study Program, Jenderal Achmad Yani Yogyakarta University, conducted a Goal Setting Training (GST), in order to improve career decisions for students. Participants who took part in the training totaled 23 students of class XII SMA. GST is given to participants online through a zoom meeting with a duration of 4 hours. Data analysis used Parametric Paired Samples Test which shows that Goal Setting Training can improve students' Career Decisions (t = -2.832, p = 0.016 <0.05). The conclusion of the training is that GST can improve the career decisions of class XII students of SMA Muhammadiyah Al Mujahidin Gunungkidul.